(untitled) (Research, Society and Development, 2022)
We recognize society’s knowledge that since the beginning of time natural resources, such as plants, have been used to supply the needs of men, both in food and health care. Morinda citrifolia, is a plant related to several biological activities, among them the antibacterial one. The present work aimed to analyze the antibacterial activity of extracts from the leaf, bark and pulp of M. citrifolia against strains of Sthaphylococcus aureus and Escherichia coli. The extracts were obtained by maceration, evaporation and subsequent resolubilization. For antibacterial activity analysis, the diffusion method was performed on filter paper discs soaked with 20μl of the extracts, using Escherichia coli (ATCC 35218) Staphylococcus aureus (ATCC BAA-97). None of the extracts showed antibacterial action against Staphylococcus aureus and only the extract of Morinda citrifolia pulp showed mild activity against Escherichia coli strain. The phytochemical prospection found saponins, alkaloids, tannins and coumarins in the leaf, alkaloids in the bark and coumarins and alkaloids in the pulp. We conclude that among the parts of the Morinda citrifolia plant analyzed, the only one that showed antimicrobial action, not highlighted, against one of the bacteria tested (E.coli) was the pulp and we can also conclude that the extracting solvent as well as the metabolites of the composition are important and influential in the researched activity.